INTERACTION STUDY OF CERTAIN DYES LIKE FERRIC OXIDE RED, BRILLIANT BLUE AND SOY FOOD STUFFS WITH STATINS AND ITS INFLUENCE ON PROTEIN BINDING AND INTRINSIC ASSOCIATION CONSTANT ‘K’ OF STATINS (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Interaction of Atorvastatin, Simvastatin and Rosuvastatin with dyes like ferric oxide red, brilliant blue and soy food stuffs were carried out in BSA using RP-HPLC method. Developed method was validated as per ICH Guidelines. Protein binding and Intrinsic association constant ‘K’ of statin drugs were calculated in presence of dyes and food stuffs. The order of interaction in Atorvastatin, Simvastatin and Rosuvastatin were found to be ferric oxide > soy food stuffs > brilliant blue; Soy food stuff > ferric oxide > brilliant blue; brilliant blue > soy food stuffs > ferric oxide red respectively. Protein binding of Atorvastatin was found to be decreased by 46.16%, 38.91%, and 30.87% in presence of brilliant blue, ferric oxide and soy food stuffs respectively. In case of Simvastatin it was found to be decreased by 35.52%, 34.63% and 18.45% and in case of Rosuvastatin it was found to be decreased by 65.29%, 56.02%, 45.81% in presence of brilliant blue, ferric oxide red and soy food stuffs respectively. The intrinsic association constant of Atorvastatin, Simvastatin, and Rosuvastatin was found to be altered in presence of brilliant blue, ferric oxide red and soy food stuffs.